If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3c + -11 = 7c + 19 Reorder the terms: -11 + 3c = 7c + 19 Reorder the terms: -11 + 3c = 19 + 7c Solving -11 + 3c = 19 + 7c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-7c' to each side of the equation. -11 + 3c + -7c = 19 + 7c + -7c Combine like terms: 3c + -7c = -4c -11 + -4c = 19 + 7c + -7c Combine like terms: 7c + -7c = 0 -11 + -4c = 19 + 0 -11 + -4c = 19 Add '11' to each side of the equation. -11 + 11 + -4c = 19 + 11 Combine like terms: -11 + 11 = 0 0 + -4c = 19 + 11 -4c = 19 + 11 Combine like terms: 19 + 11 = 30 -4c = 30 Divide each side by '-4'. c = -7.5 Simplifying c = -7.5
| 3-7x-x=-1 | | 6(1+6b)minus-8=106 | | -5x+12=6 | | -11-5a=6(5a+14) | | 8(3x+5)-(7x-2)=8 | | -3-6x=-5-4x | | 6(1+6b)-8=106 | | 2r=8r-30 | | 8-3a=2 | | 3r+2=3r+2 | | 3x-30y=-6 | | -11-2v=5-6v | | 2b-7=19 | | 14-b=2b-7 | | 2(3x-4)=10x-20 | | 45-5a=-10a | | (5x^2+6x)(20x^2-11x-3)=0 | | 5(6-4n)=n+21 | | 28+28m=-5(3m+2) | | -5n+8=-6n+1 | | 3x-4-1=10 | | -2m-5(m+8)=-96 | | -27+6y=3(y+3) | | 6-8(7k+5)=21-k | | -3(4-2k)+5= | | 6x-6-5=8x+3 | | -5+4(1+6n)=-169 | | 0=4+x/5 | | -31=26+a | | -31=26 | | 21b=14b-7 | | r+5=15-r |